Вплив святоотцівської спадщини і святих Православної Церкви на формування богословської думки архимандрита Софронія Сахарова - Sydorak, Andriy (Vox Patrum, 2018)
In his article, the author considers the main patristic sources and works of Orthodox saints, that were crucial in the formation of a well-known Orthodox theologian and spiritual seeker of the XX century the Archimandrite Sophrony Sakharov. He also reaches his writings, as well as the works and memoirs of contemporaries, to show what was the archimandrite’s relationship to the heritage of the Holy Fathers, and which texts were most relevant to him. The author pays special attention to the role of the elder Silouan, Sakharov’s spiritual mentor, who formed his patristic theology vision.